Pengaruh Komunikasi, Lingkungan Kerja dan Motivasi Terhadap Kinerja Pegawai (Pada Dinas Penanaman Modal,PTSP Dan Tenaga Kerja Probolinggo) - Cholifatur Ramadhani Aryadi; Hadi Sunaryo; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACT This research was conducted at the Department of Investment, PTSP, and Probolinggo Manpower. The purpose of this study was to examine and analyze the influence of communication, work environment and motivation on employee performance at the Department of Investment, PTSP, and Probolinggo Manpower. The variables used are communication, work environment, and motivation as independent variables, while employee performance variables are the dependent variable. The sample used in this study were 60 employees of the Investment Service, PTSP, and Probolinggo Manpower. The study used descriptive statistical analysis and inferential statistics. Data collection method by collecting primary data. The analysis used includes instrument testing, normality test, multiple linear regression analysis, classical assumption test, hypothesis testing and determination coefficient test. The results showed that the communication variables had a significant effect on the performance of the employees of the Probolingo Investment Service, PTSP, and Probolingo Manpower, while the work environment and motivation variables did not have a significant effect on the employee performance of the Probolingo Investment Service, PTSP, and Probolingo employees.Keywords : communication, work environment, motivation, and performance.